Special Issue: Tracing the Arctic; Arctic Traces - Gustafsson Reinius, Lotten (Journal of Northern Studies, 2021)
Nowhere on earth is global warming happening as fast today as in the northernmost region. In many cases the situation is acute for both humans and other animals. But it is not only biotopes, but also long-since intertwined systems of nature and culture that are in accelerating processes of change. What was once portrayed as almost invincible is now associated with vulnerability. The situation is one of urgency for the four million people living in Arctic areas, but it may ultimately affect many more. The northernmost area on earth once again reminds us that humanity too has a limit. This introduction starts with a fieldwork note from contemporary Greenland, where the contested colonial heritage also exemplifies the entanglement and friction of global interests and environmental change. In this broadly multidisciplinary collection of scholarly articles the Arctic will be discussed both as nature and as culture, and in ways that stress change and complexity. Unexpected alliances and tentacular methods are crucial in our challenging times, according to environmentalist Donna Haraway. The contributions of this journal issue also share the context of support for a co-curated exhibition at the Nordiska museet on “The Arctic—While the Ice Is Melting” (from 2019).